Jobs-Housing Balance Dimension in the New Resettlement Areas Affected by the Hydropower Construction Project Case of: Samavkhyxay Village, Xieng Ngeun District, Luang Prabang Province: https://doi.org/10.69692/SUJMRD090190 - VORRABOUTH, Beeno; VONGPRASEUTH, Thanusorn; Daravong, Sinthavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This study was conducted in Samackhysay Village, Xiengngun District, Luang Prabang Province, emphasizing the dimension of jobs-housing balance in the new resettlement areas of residents affected by the hydropower construction project and the resettlement process. 655 households have been moved from 10 villages. The methodology of the study employed a questionnaire with 250 households. The quantitative and qualitative approaches have been utilized with Binary Logistic Model in order to examine the relationships between housing and workplaces/balancing dimensions. Results of this study revealed that after the resettlement was completed, there are some positive and negative impacts illustrated, for instance, the community-level infrastructure has been updated with roads, schools, clinics, electricity, and water supply for the positive manners. Regarding the negative image, people are hard adapting to the new environment, the shortage of agricultural land and workplaces have been located far away from their residences, and their expenses increased with their longer trips to workplaces. The results also confirmed that the imbalance factor between jobs-housing is a crucial dimension of the resettlement of new locations. The Logistic Model revealed some critical issues regarding the inequalities of ethnicity, location of the original village, level of education, occupation, distance to the workplace, income, and conditions of homes and vehicles. The obvious change is that new occupations in the new resettlement area are workers compared to farmers. The outcomes of the study can be used as a guideline for creating a balance between housing and workplaces, especially the allocation of agricultural areas and the provision of occupations that are appropriate for the people to create a balance, to become the model village for the development and sustainability in the future.